2023
DOI: 10.3390/mi14081535
|View full text |Cite
|
Sign up to set email alerts
|

FinFET 6T-SRAM All-Digital Compute-in-Memory for Artificial Intelligence Applications: An Overview and Analysis

Waqas Gul,
Maitham Shams,
Dhamin Al-Khalili

Abstract: Artificial intelligence (AI) has revolutionized present-day life through automation and independent decision-making capabilities. For AI hardware implementations, the 6T-SRAM cell is a suitable candidate due to its performance edge over its counterparts. However, modern AI hardware such as neural networks (NNs) access off-chip data quite often, degrading the overall system performance. Compute-in-memory (CIM) reduces off-chip data access transactions. One CIM approach is based on the mixed-signal domain, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…It is reported that Gaussian doped JL FinFET 6T SRAM cell has improved the read/write access time. Waqas et al [121] has investigated FinFET 6T-SRAM cell to observe the noise margins, read operation, and write operation as these performance measurement parameters are very significant in digital circuit design. They varied the V th , and drain bias, and scaled the device dimensions to get an optimized value of power, area, and performance.…”
Section: A Digital Circuit Interactionmentioning
confidence: 99%
“…It is reported that Gaussian doped JL FinFET 6T SRAM cell has improved the read/write access time. Waqas et al [121] has investigated FinFET 6T-SRAM cell to observe the noise margins, read operation, and write operation as these performance measurement parameters are very significant in digital circuit design. They varied the V th , and drain bias, and scaled the device dimensions to get an optimized value of power, area, and performance.…”
Section: A Digital Circuit Interactionmentioning
confidence: 99%